COVID-19 IMPACTS ON ENPLOYMENT RATE IN HOSPITALITYINDUSTRY (Journal of Media studies, 2021)
The intention of the article is to present a general review of theextent to which pandemic and confinement endeavours to halt the virus spreadhave affected the world of work, international economic domains, as well asbusinesses involving hospitality and tourism sectors. The focus is particularlyplaced on several countries, namely, Spain, Germany, the USA, and Kazakhstan.In practical application, the article can be beneficial for practitioners as itpresents global experiences and feasible strategies to cope with futureunforeseen circumstances such as pandemic threat.